Theology as science? The position of Christian theology within an academic setting - Louw, DJ (Nederduitse Gereformeerde Teologiese Tydskrif, 2004)
Within an academic setting, the traditional tension between faith and reason is always at stake. It is argued that in terms of the hermeneutical paradigm, theology could be viewed as a science. Instead of an explanatory model or even a positivistic model with its emphasis on verification and falsification, a hermeneutical model opts for understanding and interpretation wherein the human quest for meaning plays a decisive role. Theology should be defined in terms of a fourfold description which takes critical reflection, communication, action and hope as ingredients of a scientific approach seriously: fides quaerens intellectum; fides quaerens verbum; fides quaerens actum; fides quaerens spem.